Genetic tracking of density‐dependent adult recruitment: A case study in a subtropical oak. (18th March 2021) - Tong, Xin; Nason, John D.; Ding, Yuan‐Yuan; Chen, Xiao‐Yong
Abstract: Density‐dependent recruitment is fundamental to understanding species diversity and community dynamics in plants. Although there is compelling evidence that seeds and seedlings die from conspecific negative density dependence (CNDD) as predicted by the Janzen–Connell hypothesis, characterising adult recruitment remains a challenge for long‐living trees. Previous studies have used the decrease in fine‐scale spatial genetic structure (FSGS) across life stages to indicate CNDD; however, this has not been tested rigorously. We addressed these challenges by integrating dispersal kernels and FSGS. To establish links between density dependence and FSGS, we simulated seedlings based on the estimated dispersal kernels from parentage analyses, and further simulated adults under various seedling‐to‐adult recruitment scenarios, using an individual‐based spatially explicit model. We tested this method in an isolated Cyclobalanopsis glauca population on China's Dajinshan Island. We detected significant FSGS in the seedlings and weaker, though also significant, FSGS in the adults. As expected, the observed FSGS of seedlings was well predicted by the simulated seedlings, with observations falling inside the 95% confidence envelopes over all distance classes. However, the simulations showed that CNDD enhanced the FSGS while positive density dependence dampened it during the seedling‐to‐adult transition. The adult FSGS of our population was therefore explained by positive rather than negative density‐dependent adult recruitment. Synthesis . Our study demonstrates that the change of FSGS in conjunction with dispersal‐based model tests can offer a valuable insight into density‐dependent adult recruitment. The results indicate that the transitions from seedlings to adults in C. glauca are dominantly regulated not by Janzen–Connell effects, but by processes of positive density dependence. More broadly, the findings may provide a caution against extrapolations of widespread Janzen–Connell effects in seeds and seedlings to adult recruits, underscoring a critical gap between mechanisms at early stages and long‐term population and community dynamics. Abstract : Density‐dependent adult recruitment is necessary for the Janzen−Connell mechanism to regulate plant population and community dynamics, but has rarely been examined. We present an integrative method by combining dispersal kernels and fine‐scale spatial genetic structure to test density dependence in adult recruitment. The results reject the dominant role of Janzen−Connell effects in a Cyclobalanopsis glauca population. 摘要: 阐明密度制约更新效应是理解植物群落物种多样性和群落动态的基础。如Janzen–Connell假说所预测，广泛证据表明种子和幼苗的更新易受同种负密度制约作用，但成体更新是否存在密度制约仍难知晓。前期研究以小尺度空间遗传结构随植物发育的衰减表征同种负密度制约效应，但这一关联尚未得到验证。 为建立密度制约与空间遗传结构的直接联系，我们提出：采用基于个体的空间明晰模型，以亲本分析估计的扩散核函数为基础模拟幼苗遗传结构，进而模拟不同更新模式塑造的成体空间遗传结构。我们运用该方法研究中国大金山岛青冈种群成体更新的密度制约效应。 幼苗存在显著的空间遗传结构，其观测值在所有距离等级均处于模型预测的95%置信区间内。与幼苗相比，成体表现出显著但较弱的空间遗传结构。模拟结果显示，在幼苗成长至成体过程中，同种负密度制约将增强空间遗传结构，正密度制约则减弱遗传结构。该种群成体遗传结构与成体更新正密度制约效应模型的预测结果相吻合。 本研究提出并验证了基于扩散对小尺度空间遗传结构的变化进行模型检验可揭示成体更新的密度制约效应。结果表明，青冈种群幼苗发育至成体主要受正密度制约过程调节，而非Janzen–Connell效应。将种子和幼苗中广泛存在的Janzen–Connell效应简单外推至成体更新可能会高估这一机制对植物群落物种多样性维持的贡献。成体更新应是完成从发育早期阶段的生态机制到长期的种群和群落动态不可或缺的一环。